Relative chlorophyll contents in the evaluation of the nutritional status of nitrogen from xaraes palisade grass and determination of critical nitrogen sufficiency index - Costa, João Paulo Ramos [UNESP]; Caputti, Gregory De Paula [UNESP]; Galzerano, Leandro; Silva, Wilton Ladeira Da [UNESP]; Ruggieri, Ana Claudia [UNESP]; Malheiros, Euclides Braga [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2015)
The nutritional status of xaraes palisade grass with SPAD chlorophyll meter and the critical nitrogen sufficiency index (cNSI) in the dry and rainy seasons were assessed. The experiment was conducted in a completely randomized design with four treatments (50, 100, 200 and 400 kg N ha-1), three replicates and two seasons: dry and rainy. All variables had a high nonlinear relationship with their predictors (p < 0.001). Total nitrogen (TN) reached a plateau at doses 262.0 and 514.8 kg of N ha-1 and the concentration of TN in the plant was 1.88 and 1.93% respectively during the rainy and dry season. Relative chlorophyll content (RCC) reached a plateau at 46.05 and 53.65 SPAD units in the rainy and dry seasons, respectively. The production of dry matter (DM) showed maximum response to nitrogen fertilization at 209.5 and 229.1 kg N ha-1 during the rainy and dry season respectively. The nitrogen sufficiency index (NSI) reached the plateau at 0.85 and 0.99 in the rainy and dry season respectively. All variables showed high linear correlation (r = 0.71 to 0.99). The xaraés palisade grass's cNSI is 0.85 and the chlorophyll meter may be used as a nutritional N management tool for the grass.

Objetivou-se avaliar o estado nutricional do capim-xaraés utilizando o clorofilômetro SPAD e estabelecer o índice de suficiência crítico (ISNc) nas épocas das águas e seca. O experimento foi conduzido em um delineamento inteiramente casualizado com quatro tratamentos (50, 100, 200 e 400 kg N ha-1), três repetições, duas épocas: águas e seca. Todas as variáveis apresentaram alta relação não linear com seus preditores (p < 0,001). O nitrogênio total (NT) alcançou o platô na dose de 262,0 e 514,8 kg de N ha-1 e a concentração de NT na planta foi 1,88 e 1,93% no período das águas e seco, respectivamente. O teor relativo de clorofila (TRC) atingiu o platô a 46,05 e 53,65 unidades SPAD no período das águas e seca, respectivamente. A produção de matéria seca (MS) apresentou máxima resposta a adubação nitrogenada na dose de 209,5 e 229,1 kg N ha-1 na época das águas e seca, respectivamente. O índice de suficiência de nitrogênio (ISN) atingiu o platô em 0,85 e 0,99 na época das águas e secas respectivamente. Todas as variáveis apresentaram alta correlação linear (r= 0,71 a 0,99). O ISNc do capim-xaraés é 0,85 e o clorofilômetro pode ser utilizado como ferramenta de manejo nutricional de N para essa gramínea.
Teor relativo de clorofila na avaliação do status nutricional denitrogênio do capim-xaraés e determinação do índice de suficiência do nitrogêniocrítico
Keywords: fertilization: Urochloa brizantha; chlorophyll meter: nutritional status: SPAD.; adubação; Urochloa brizantha; clorofilômetro; estado nutricional; SPAD